UTX/Top2β axis mediated spinal cord microvascular endothelial cells senescence exacerbates spinal cord injury - Dongliang Liu; Yudong Liu; Tianding Wu; Jianzhong Hu (PLoS ONE, 2025)
Background Cellular senescence plays a critical role in regulating angiogenesis. While UTX has been implicated in vascular regeneration following spinal cord injury (SCI), its underlying mechanisms remain incompletely understood. This study investigates how senescence mediates UTX-regulated vascular responses after SCI. Methods We assessed p16 INK4a (a senescence marker) and UTX expression in spinal cord endothelial cells at 3, 5, 7 and 14 days post-SCI. By breeding UTX flox/flox mice with heterozygous Tek-Cre mice, we generated endothelial-specific UTX knockout mice. Cellular senescence and proliferation were evaluated in primary spinal cord microvascular endothelial cells (SCMVECs). RNA sequencing and chromatin immunoprecipitation (ChIP)-seq were performed to identify UTX target genes. Results UTX and p16 INK4a expression were both elevated post-SCI in a time-dependent manner. UTX deletion reduced endothelial senescence and enhanced proliferation both in vivo and in vitro. RNA-seq and ChIP-seq identified Top2β as a direct transcriptional target of UTX, negatively regulated through promoter binding. These findings were validated by ChIP-qPCR, western blotting, and immunofluorescence. Knockdown of Top2β reversed the anti-senescence and pro-proliferative effects induced by UTX deletion. Conclusions UTX deletion attenuates vascular endothelial senescence and promotes angiogenesis after SCI by upregulating Top2β expression. This newly defined UTX/Top2β axis regulates vascular regeneration and represents a potential therapeutic target for promoting vascular repair following SCI.